Facilitating Access to Information Through Collaboration: Examination of the Role of Collaborative Technology in Competitive Intelligence - Jin, Tao; Bouthillier, France (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Few attempts have been made to establish conceptual links between collaboration, collaborative technology, information access and competitive intelligence. The purpose of this paper is to propose a framework and a number of starting premises for studying collaboration and the role of collaborative technology in the context of competitive intelligence. Peu de tentatives ont été faites pour établir des liens conceptuels entre les notions de collaboration, technologie de collaboration, accès à l’information et veille concurrentielle. L’objectif ici est de proposer un cadre d’analyse et plusieurs prémisses utiles pour l’étude du concept de collaboration et le rôle de la technologie supportant cette activité dans le cadre de la veille concurrentielle.